2018 White Paper on Recent Issues in Bioanalysis: focus on flow cytometry, gene therapy, cut points and key clarifications on BAV (Part 3 – LBA/cell-based assays: immunogenicity, biomarkers and PK assays). (29th November 2018) - Stevenson, Lauren; Richards, Susan; Pillutla, Renuka; Torri, Albert; Kamerud, John; Mehta, Devangi; Keller, Stephen; Purushothama, Shobha; Gorovits, Boris; Litwin, Virginia; Stebbins, Christopher; Marini, Joseph; et al.
The 2018 12 th Workshop on Recent Issues in Bioanalysis took place in Philadelphia, PA, USA on April 9–13, 2018 with an attendance of over 900 representatives from pharmaceutical/biopharmaceutical companies, biotechnology companies, contract research organizations and regulatory agencies worldwide. WRIB was once again a 5-day full immersion in bioanalysis, biomarkers and immunogenicity. As usual, it was specifically designed to facilitate sharing, reviewing, discussing and agreeing on approaches to address the most current issues of interest including both small- and large-molecule bioanalysis involving LCMS, hybrid LBA/LCMS and LBA/cell-based assays approaches. This 2018 White Paper encompasses recommendations emerging from the extensive discussions held during the workshop and is aimed to provide the bioanalytical community with key information and practical solutions on topics and issues addressed, in an effort to enable advances in scientific excellence, improved quality and better regulatory compliance. Due to its length, the 2018 edition of this comprehensive White Paper has been divided into three parts for editorial reasons. This publication (Part 3) covers the recommendations for large molecule bioanalysis, biomarkers and immunogenicity using LBA and cell-based assays. Part 1 (LCMS for small molecules, peptides, oligonucleotides and small molecule biomarkers) and Part 2 (hybrid LBA/LCMS for biotherapeutics and regulatory agencies' inputs) are published in volume 10 of Bioanalysis, issues 22 and 23 (2018), respectively.